Development of Criminal Concepts and Criminal in Corruption Criminal Cases in Indonesia - Salsabilla Harahap, Athika; Mutiara Nelson, Febby (Journal of World Science, 2023)
This study aims to discover the concepts of crime and punishment in corruption cases in Indonesia today along with their problems and to provide suggestions for new criminal and punishment concepts in Indonesia for the future seen from the development of criminal and sentencing theories. Corruption in Indonesia is better known as a crime that is detrimental to the country's finances and economy. That it has an impact on hampering the growth and continuity of national development, so severe eradication must be carried out so that it has become necessary to establish appropriate criminal and criminal concepts in dealing with criminal acts. Corruption crime. This research is normative-juridical legal research that emphasizes statutory and conceptual approaches. In this study, it was concluded that the crimes and punishments contained in corruption crimes are currently ineffective in achieving the desired sentencing goals, so it is necessary to make changes to them by looking at the development of criminal and sentencing concepts that have developed at this time. This is important so that the goals of sentencing that have been aspired to can be achieved.